2005
DOI: 10.1016/j.ejvs.2004.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Markers of Coagulation Activation, Endothelial Stimulation and Inflammation in Patients with Peripheral Arterial Disease

Abstract: Coagulation activation and endothelial stimulation are significantly increased in patients with peripheral arterial disease compared to healthy controls. Coagulation and endothelial activation increases with the severity of the arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
64
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 28 publications
3
64
0
2
Order By: Relevance
“…[24][25][26][27] In the present study, most of the patients had levels of emerging risk factors higher than those associated with increased risk of vascular events. [21][22][23] Probably the most interesting finding is that the ABI was inversely correlated with LDL-C levels in patients not treated with lipid-lowering drugs.…”
Section: Discussionmentioning
confidence: 78%
“…[24][25][26][27] In the present study, most of the patients had levels of emerging risk factors higher than those associated with increased risk of vascular events. [21][22][23] Probably the most interesting finding is that the ABI was inversely correlated with LDL-C levels in patients not treated with lipid-lowering drugs.…”
Section: Discussionmentioning
confidence: 78%
“…26 It is also known that patients with peripheral artery disease have increased levels of inflammation markers. 27 Elevated levels of CRP have been associated with poor long-term prognosis in patients with peripheral artery disease. 28 Our study had some limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Other conditions that promote a systemic inflammatory response and may predispose the arterial vessels of the lower limbs to atherosclerosis are infections and systemic diseases, such as rheumatoid arthritis and systemic lupus erythematosus. Whatever the inflammatory trigger, a large number of cross-sectional and longitudinal studies have demonstrated a close link between inflammation and PAD (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Notably, each of the inflammatory molecules investigated in these studies is not simply a marker of inflammation but plays an active role in peripheral atherogenesis (46)(47)(48)(49)(50)(51)(52)(53).…”
Section: Inflammationmentioning
confidence: 99%
“…Inflammation plays a role in the initiation and progression of PAD, and in coronary artery disease (CAD) (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). There are several candidate inflammatory markers, including traditional risk factors that play a pro-atherogenic role, at least in part, through an inflammatory mechanism.…”
Section: Inflammationmentioning
confidence: 99%